PBG 13. Efficacy of Selected Corn (Zea mays, L.) genotypes for resistance to Asian corn borer (Ostrinia furnacalis, Guenee) (The Philippine Journal of Crop Science, 2018)
Simultaneous laboratory and screen cage studies were conducted to assess the efficacy of selected corn genotypes against Asian corn borer (ACB). Twenty-six corn genotypes which consisted of local corn accessions, foreign corn accessions, recycled commercial seeds (RCS), non-genetically modified (GM) open-pollinated varieties (OPV), non-GM hybrids, non-Bt glyphosate-tolerant hybrid and Bt hybrids were evaluated. Plant resistance indices such as leaf disc and stalk feeding larval survivability, stalk tunnel length and leaf damage were observed. Leaf disc and stalk feeding larval survivability revealed that the four tested Bt hybrids were resistant to ACB larvae, having complete larval mortality. Multivariate analysis grouped eight genotypes (RCS 2, RCS 4, RCS 5, IPB Var 13 (non-GM OPV), and four Bt hybrids) as highly resistant based on laboratory (larval survivability and tunnel length) and screen cage (damage rating and stalk tunnel length) studies. Resistant genotypes were attacked by ACB mostly below the ear nodes, while the damage observed from intermediate and susceptible genotypes were distributed throughout the entire corn plant. Larval survivability based on laboratory stalk feeding method was highly correlated with field total stalk damage area (r=0.73; p<0.001) indicating a close relationship between the presence of the ACB and visible damage to corn plants. Significant positive correlation between the laboratory larval survivability based on leaf disc feeding method and field visual leaf damage ordinal rating (r=0.60; p<0.001) was also observed suggesting that the latter rating system is also a reliable measure especially for detecting antibiosis or antixenosis mechanism against ACB larva from corn genotypes. Notably, IPB Var 13 and Bt hybrids had comparably high larval mortality. Hence, further evaluation of the morphological and biochemical attributes underlying the natural resistance of IPB Var 13 is necessary.